Attitude Of Teachers In Higher Education Institutions Towards Online Teaching And Learning - Paladan, Nerisa (CV. Inara, 2022)
The sustainability of higher education institutions (HEI) to provide quality education was challenged during and after the covid-19 pandemic in adopting the new normal. Attitude is one factor in embracing the new normal in the higher education teaching modalities. This study aims to assess the higher education institutions’ teachers’ attitudes toward online teaching and learning. It will specifically know the difference between the attitude of a private and public HEI teacher and distinguish the attitude of HEI teachers according to gender, academic rank, and the number of years in teaching. Quantitative research was utilized; a sample of 107 HEI teachers are the respondents of this study; they voluntarily participate in the self-administered survey using an online google form and it uses a standardized questionnaire in assessing teachers’ attitude in the HEI when dealing with online teaching and learning. The results of the statistical test revealed no significant difference in the attitude of HEI teachers and have an overall favorable attitudetowards online teaching and learning with regards to their gender and number of years in teaching. However, there is a significant difference in attitude according to the type of HEI under the responsiveness towards online education with a P-value of 0.004, and academic rank under the appreciation for online teaching and learning with a P-value of 0.037. Post hoc test shows a significant difference in attitude of community colleges with a mean of 3.44, a favorable attitude, and state universities with a corresponding mean of 3.13, a neutral attitude on online teaching and learning. That HEI teachers have an overall favorable attitude in terms of appreciation for online teaching and learning, responsiveness towards online education, proficiency in handling online teaching, and knowledge of technological reforms which indicates their readiness toward future-oriented higher education.